2012
DOI: 10.1097/nmd.0b013e31825bfb53
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Neuroticism and Extraversion

Abstract: Neuroticism and extraversion are potentially important markers of personality vulnerability to suicide. Whereas previous studies have examined these traits independently, we examined their combined effects. Data were collected from family members and/or friends of individuals 18 years or older who died by suicide (n = 64) in rural China and from age-, sex-, and geographically matched controls (n = 64). Personality was assessed with the NEO-Five Factor Inventory. Individuals with a personality style characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…While our findings fit our hypothesis for passive coping [59], we expected that higher levels of neuroticism would be related to suicide risk [41,42]. One could speculate that higher levels of neuroticism and passive coping may also protect against suicide in a similar way to negative symptoms.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…While our findings fit our hypothesis for passive coping [59], we expected that higher levels of neuroticism would be related to suicide risk [41,42]. One could speculate that higher levels of neuroticism and passive coping may also protect against suicide in a similar way to negative symptoms.…”
Section: Discussionsupporting
confidence: 74%
“…In the general population, higher levels of neuroticism may increase the risk for suicide [41]. In addition, higher levels of neuroticism seem to predict future onset of psychotic disorders [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high levels of neuroticism and low levels of extraversion have been significantly associated with suicidality in a general population sample (Fang et al , 2012). Congruent studies have shown that higher levels of extraversion predict a lower risk for suicide, whereas introversion increases suicide risk (Roy, 2003, Tsoh et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, given the consistent association of psychopathology (e.g., depression) with suicidal ideation and attempt (Beautrais 1999), it is imperative that research adjust for comorbid diagnoses to avoid conflating suicidal ideation and attempt with related psychopathological syndromes. Similarly, Kendler and colleagues, among others, have demonstrated the role of stressful life events in suicidal ideation and behavior, specifically attempted suicide (Statham et al 1998; Fergusson et al 2000; Roy 2003a, 2003a; Fanous et al 2004; Bi et al 2012; Fang et al 2012; Zhu et al 2013; Chan et al 2014). Neuroticism may increase the risk to experience stressful life events or to perceive life events as stressful (Kendler et al 2003; Pickles et al 2010).…”
mentioning
confidence: 90%